TEACHERS’ PROFESSIONAL COMMITMENT FROM THE PERSPECTIVE OF EMPOWERMENT AND TRUST - Sabrina Dachmiati; Bibin Rubini; Griet Helena Laihad (Yayasan Education and Social Center, 2026)
Professional commitment is an essential aspect that teachers need to continuously develop in order to perform their roles effectively and maintain educational quality. However, several factors may influence the level of teachers’ professional commitment, particularly empowerment and trust. This study aimed to determine whether empowerment and trust have significant effects on teachers’ professional commitment. The research was conducted among public junior high school teachers in Bogor City. A total of 184 teachers were selected as respondents through a multistage random sampling technique, while the sample size was determined using the Slovin formula. Data regarding professional commitment, empowerment, and trust were collected using measurement scales that had previously passed validity and reliability testing. The research hypotheses were analyzed using multiple linear regression with the assistance of SPSS software. The findings revealed that both empowerment and trust significantly influence teachers’ professional commitment. Therefore, strengthening these factors may enhance commitment. Further studies are recommended to explore specific indicators of empowerment and trust related to teachers’ professional commitment.